Regulation of gluconeogenesis by Aldo-keto-reductase 1a1b in zebrafish - Li, Xiaogang; Schmöhl, Felix; Qi, Haozhe; Bennewitz, Katrin; Tabler, Christoph Tobias; Poschet, Gernot; Hell, Rüdiger; Volk, Nadine; Poth, Tanja; Haußer-Siller, Ingrid; Morgenstern, Jakob; Fleming, Thomas; et al. (iScience, 2020)
Regulation of glucose homeostasis is a fundamental process to maintain blood glucose at a physiological level, and its dysregulation is associated with the development of several metabolic diseases. Here, we report on a zebrafish mutant for Aldo-keto-reductase 1a1b (akr1a1b) as a regulator of gluconeogenesis. Adult akr1a1b−/− mutant zebrafish developed fasting hypoglycemia, which was caused by inhibiting phosphoenolpyruvate carboxykinase (PEPCK) expression as rate-limiting enzyme of gluconeogenesis. Subsequently, glucogenic amino acid glutamate as substrate for gluconeogenesis accumulated in the kidneys, but not in livers, and induced structural and functional pronephros alterations in 48-hpf akr1a1b−/− embryos. Akr1a1b−/− mutants displayed increased nitrosative stress as indicated by increased nitrotyrosine, and increased protein-S-nitrosylation. Inhibition of nitrosative stress using the NO synthase inhibitor L-NAME prevented kidney damage and normalized PEPCK expression in akr1a1b−/− mutants. Thus, the data have identified Akr1a1b as a regulator of gluconeogenesis in zebrafish and thereby controlling glucose homeostasis.
Gesehen am 22.02.2021